Analysis of Students’ Questioning Skills on the Problem Based Learning Model of Biology Subjects at Nurul Iman High School Palembang - Elsi Aryanti; Jumhur Jumhur; Ummi Hiras Habisukan (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2019)
Question skill is skill that must be ask by students in learning to get information from their interlocutor. In the biology learning, question skill is necessary for interaction between teacher and student so that learning is good. The study aims to describe the questioning skills of class XI even semester 2018/2019 in SMA Nurul Iman Palembang based on Bloom Taxonomy Revised Cognitive Process Dimensions through the Problem Based Learning model of Biology subjects. The research was conducted at SMA Nurul Iman Palembang. This research was conducted in April-May 2019. This research method is qualitative descriptive. Data collection used observation, interview, and documentation. Data analysis techniques used according to Miles and Huberman and then triangulation of the results of observation, interview, and documentation. The results showed that the questioning skills of class XI even semester 2018/2019 in SMA Nurul Iman Palembang based on Bloom Taxonomy Revised Cognitive Process Dimensions through the Problem Based Learning model of  respiratory system dominated by the level cognitive C2 (understanding) with 26 questions and written question with 24 questions. This showed that the questioning skills of class XI in SMA Nurul Iman Palembang through the Problem Based Learning model still relatively low